IEEE Access Special Section Editorial: Information Security Solutions for Telemedicine Applications - Singh A.K.; Lv Z.; Rho S.; Singh S.K.; Chang X.; Puech W. (My University, 2025)
Implementing telemedicine solutions has recently become a trend among various research teams at an international level. Telemedicine refers to the use of modern information and communication technologies to meet the needs of citizens, patients, healthcare professionals, and healthcare providers, as well as policy makers. Telemedicine applications are very promising and have great potential; they can play a very important role in service provision by improving access, equity and quality through connecting healthcare facilities and healthcare professionals, and diminishing geographical and physical barriers. However, the transmission and access technologies of medical information raise critical issues that urgently need to be addressed, especially those related to security. Further, medical identity theft is a growing and dangerous crime. Stolen personal information can have a negative financial impact, but stolen medical information cuts to the very core of personal privacy. Medical identity theft already costs billions of dollars each year, and altered medical information can put a person's health at risk through misdiagnosis, delayed treatment or incorrect prescriptions. Yet, the use of hand devices to store, access, and transmit medical information is outpacing the privacy and security protection on those devices. Therefore, the authenticity of the information and related medical images is of prime concern as they form the basis of inference for diagnostic purposes. In such applications, tamper proofing and guaranteed originality of medical data/information is achieved by embedding some kind of watermark(s) which must be secure and robust against malicious attacks. Robustness and security of medical data/information against attacks is an interesting, challenging area for researchers. Potential researchers are using watermarking and cryptography to disseminate security to the medical data. Further, noted researchers are using watermarking techniques in the field of healthcare to address health data management issues, including source and data authentication, efficient image archiving and retrieval, optimizing bandwidth required to transmit the data, and highlighting diagnostically significant regions. © 2013 IEEE.